Determinants Of Liquidity Risk In Banking Sector On The Indonesia Stock Exchange - Susy Muchtar, Gianvha Sena Rustimulya (Jurnal Manajemen, 2019)
This research aims to determine the factors that impact liquidity risk. The sample used in this research is a banking sector that is listed on the Indonesia Stock Exchange (IDX) in the period 2008-2017. Independent variable in this research bank size, deposits, profitability, cost of funds, asset quality, capital adequacy ratio, economic cycle, and inflation and the dependent variable is liquidity risk. The amount of the sample of the research amounted to 25 banking sector, by using purposive sampling. The result of this research indicates that bank size, profitability, cost of funds, and asset quality have a negative effect on liquidity risk, while deposits, capital adequacy ratio, economic cycle, and inflation have no impact on liquidity risk. The results of this study are expected to be used as a reference for bank managers and investors in looking at the factors that affect the liquidity risk in the banking industry.